2017
DOI: 10.1002/jemt.22823
|View full text |Cite
|
Sign up to set email alerts
|

Light‐sheet based lithography technique for patterning an array of microfluidic channels

Abstract: We propose a Light-sheet laser interference lithography technique for fabricating periodic microfluidic channels. This technique uses multiple light-sheet illumination pattern that is generated using a spatial filter at the back-aperture of the cylindrical lens. Specially designed spatial filter is used that give rise to a periodic pattern at the focal plane which is essentially a 1D Fourier transform of the spatial filter transfer function. One-dimensional focusing property of the cylindrical lens result in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Still, beside the imaging capabilities of LSFM in biological samples, different original applications can be proposed. Within this context, it has been demonstrated that light‐sheets based lithography technique offer a fast and single‐shot process to generate micro‐fluidic channels (Mohan & Mondal, ). Indeed, light sheet illumination can be implemented for laser interference lithography, thus smoothing the way to the fabrication of periodic microfluidic channels and the generation of complex microstructures.…”
mentioning
confidence: 99%
“…Still, beside the imaging capabilities of LSFM in biological samples, different original applications can be proposed. Within this context, it has been demonstrated that light‐sheets based lithography technique offer a fast and single‐shot process to generate micro‐fluidic channels (Mohan & Mondal, ). Indeed, light sheet illumination can be implemented for laser interference lithography, thus smoothing the way to the fabrication of periodic microfluidic channels and the generation of complex microstructures.…”
mentioning
confidence: 99%